Post-tonsillectomy dietary advice: systematic review. Issue 10 (24th October 2016) - Millington, A J F; Gaunt, A C; Phillips, J S
Abstract: Objective: To determine if there is evidence that post-tonsillectomy dietary advice affects post-operative morbidity. Method: A systematic review was conducted of Embase, Medline, the Cumulative Index to Nursing and Allied Health Literature and PsycInfo, to November 2014. Results: Seventeen articles were included; their heterogeneous nature prevented meta-analysis. Of these, all three small, randomised studies showed no statistical difference in morbidity between restricted and non-restricted diets. Conclusion: Most post-tonsillectomy dietary advice is based on historical anecdotes and not rigorous scientific testing. The existing small-scale, randomised studies show no statistical difference in morbidity between non-restricted and restricted diets.